Activity Based Costing in Universities - First Step of Calculation of Teaching Costs - Klaus-Rosińska, Agata; Kowalski, Michał Jerzy (Rachunek kosztów działań w szkołach wyższych - pierwszy etap kalkulacji kosztów kształcenia, 2011)
It is necessary to seek solutions supporting costs management where activity-based costing (ABC) is important especially in higher education institutions. The purpose of the article is to present the model of teaching cost calculation based on ABC, which was created by one of the departments of the Wrocław University of Technology. Because of the complexity of the model the article is divided into two related parts. This article contains the first step of calculation according to ABC.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 49-61
Keywords: activity-based costing; cost calculation; teaching costs